IMPROVING THE DIAGNOSIS OF SENSORY DISORDERS IN TRAUMATIC MIDFACIAL INJURIES ACCOMPANIED BY ORBITAL FLOOR FRACTURES - Nazarevych M.R; Pohranychna Khrystyna; Ohonovskyi R.Z; Ilnytskyi Ya.M; Danylo Halytsky (Romanian Society of Oral Rehabilitation, 2020)
Among the bone fractures of the midface, blow-out fractures amount to 11-28% and occupy the third place after zygomatic and zygomatic arch fractures and fractures of nasal bones. According to our observations izolated orbital bottom fractures occurred in 8.9% of cases. With the blow-out fracture, the presence of clinical signs of neuritis of the infraorbital nerve is an important pathognomonic symptom indicating the localization of bone fracture at the orbital floor. The main factors that determine the rate and quality of unprompted recovery of affected functions and, accordingly, the scope and target of the therapeutic interventions in cases of peripheral traumatic neuropathies include: the degree of nerve guide lesion, the level of destruction, tissue ischemia, the kind of the disturbing factor. When the nerve is constricted, the degree of conductivity failure depends primarily on the duration and intensity of constriction injury. Research objective was to improve diagnostics of traumatic lesions of infraorbital and zygomatic nerves in patients with blow-out fractures. Clinical, radiological, neurofunctional and biochemical methods of research were applied in 19 patients, aged 20 to 65 years, with blow-out fractures. The degree of destruction of infraorbital and zygomatic nerves was assessed by classification of H. Seddon (1943), which allows determining the degree of lesion of the nerve trunk according to the changes in conductivity in each of its segments. The degree of lesion of the branches of the maxillary nerve was determined according to the data of electrophysiological tests according to Nechaieva N.K. et al. (2014). Electrodiagnostics of sensitivity of skin branches of maxillary nerve was carried out in their exit sites on the surface of face using low-frequency electrotherapy device "Radius-01 FT" (Belarus) in the mode of electrical stimulation. Electroodontometry of teeth on the corresponding side of the upper jaw was carried out using a portable electroodontometer "Pulptester" (Taiwan). In the peripheral venous blood of patients, there was determined the concentration of neuron-specific enolase (NSE), which is a neuron-specific isoform of enolase found in neurons. It was analyzed by an immunochemical method with the use of electrochemiluminescent detection, using a Cobas 6000 analyzer and test system by Roche Diagnostics (Switzerland). Statistical processing of the results of research was carried out with the help of a computer program for statistical computation "Statistica 8".We found a mild degree (neuropraxia) of damage to the orbital nerve in 12 patients. The content of neuron-specific enolase in the blood did not exceed the upper limit of normal - 15.9 ± 1.4 ng / ml (p> 0.05). Sensitivity disorders of the teeth and soft tissues in the area of ​​innervation of the suborbital and zygomatic nerves in all patients in this group were temporary. The sensitivity of the damaged nerves completely recovered after 3 - 4 weeks. The presence of axonotmesis of the suborbital and zygomatic nerves in seven patients caused severe sensory disturbances in the soft tissues of the suborbital and zygomatic areas, loss of sensitivity in the upper jaw teeth on the side of the injury. These pathological changes were identified to be caused by their compression of the orbital floor by bone fragments, which were displaced into the maxillary sinus. In their blood, such patients had an increased concentration of neuron-specific enolase, which exceeded the upper limit of normal - 20.6 ± 1.7 ng / ml (p <0.01). In this category of patients, sensitivity, as a rule, completely recovered in 1,5 - 2 months after operations on reconstruction of the orbital bottom and after a course of drug therapy.The use of electrophysiological tests and study in the blood of the nervous tissue damage marker- neuron-specific enolase allow us to identify the degree of damage to the suborbital and zygomatic nerves in patients with isolated fractures of the fundus.